2015
DOI: 10.15376/biores.10.3.3979-3986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residence Time on Hydrothermal Carbonization of Corn Cob Residual

Abstract: Hydrothermal carbonization is a promising technique for conversion of industrial waste into valuable products. Producing hydrochar from corn cob residual (CCR) in a cost-effective way is key, from an economic standpoint. For this purpose, the effect of residence time in the range of 0.5 to 6 h was studied under the optimal temperature of 250 °C. Results showed that the higher heating value (HHV) of hydrochar increased approximately 40% in comparison to that of the raw material; however, prolonging the residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…3. As shown, the surface of CCR was relatively smooth while having small pores, which may have been caused by the recombination of carbon products from decarboxylation reactions and release of volatiles during the carbonization process (Liu et al 2011;Zhang et al 2015a). Figure 2b shows that a large number of microspheres were aggregated on the surface.…”
Section: Surface Morphology Studiesmentioning
confidence: 91%
“…3. As shown, the surface of CCR was relatively smooth while having small pores, which may have been caused by the recombination of carbon products from decarboxylation reactions and release of volatiles during the carbonization process (Liu et al 2011;Zhang et al 2015a). Figure 2b shows that a large number of microspheres were aggregated on the surface.…”
Section: Surface Morphology Studiesmentioning
confidence: 91%
“…These studies on HTC indicated that the physicochemical characteristics of hydrochar were dependent on the property of feedstock. In addition, the process parameters such as reaction temperature and time had a significant effect on the HTC process (Funke and Ziegler 2010;Lu and Pellechia 2013;Gao et al 2013;Zhang et al 2015). Biomass could undergo complicated chemical reactions under different process conditions including hydrolysis, dehydration, decarboxylation, and condensation polymerization during hydrothermal carbonization (Funke and Ziegler 2010;Sevilla et al 2011;Kang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of activation on the functional groups of hydrochars was then examined using FTIR, as shown in Figure 3. Results showed reduction of peak strength of the functional groups in all waste biomass samples due to volatilization and degradation [30,43]. Coffee waste grounds (CWG) and RH showed a relatively higher degree of functional group degradation compared to corncobs (CC) and coconut sawdust (SD).…”
Section: Activationmentioning
confidence: 99%